FAKTOR FAKTOR YANG MEMPENGARUHI KEPUTUSAN PETANI DALAM PEREMAJAAN KARET DI KECAMATAN PEMAYUNG KABUPATEN BATANG HARI - Saputri, Karlina; Murdy, Saad; Fathoni, Zakky (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2018)
This research was conducted to determine the factors that influence the decisions of farmers on replanting of the rubber in district Pemayung Batang Hari Regency. The Decision in this research is the choice by the farmer doing replantling or not doing replanting of the rubber. The sampling method used proportional random sampling method with the number of respondents as much as 75 people with the allocation of 38 people do replanting and 37 people don’t do replanting. Data analysis used the method of binary logistic regression analysis approach. Expected factor influence replanting decisions of the rubber are age, leve of education, number of family member, plantation area, capital and income. The results showed that there are two factors with the level of error (5%) that affect significantly the replanting decision of the rubber in district Pemayung Batang Hari Regency. The factors mentioned include the number of capital and income. Whereas with level of error (10%) that there are three factors that affect significantly, the factors mentioned include the number of family members, capital and income. It showed that the factors of age, level of education, number of family member and plantation area has no effect against the decision of farmers in the replanting of the rubber in district Pemayung Batang Hari Regency. The famers decision on choosing replanting in district Pemayung supported by the government province support that gives help as a stimulator for farmers responden, the helps by the government consist of seeds and fetilizer.